Research on fish species composition in Tam Giang - Cau Hai lagoon, Thua Thien - Hue province - Hoang, Nguyen Van; Duc, Nguyen Huu (Academia Journal of Biology, 2012)
The Tam Giang - Cau Hai lagoon is the biggest one in Southeast Asia of 70 kilometers long and the total area of 248 square kilometers. It plays a very important role in the economy, culture and ecotourism in Thua Thien - Hue province and especially, it is of a great scientific value. However, it has been being threatened due to over exploiting and aquaculture. Many constructions, such as, hydroelectric Plant on Huu Trach branch and in A Luoi district, water reservoir in Ta Trach branch, Thao Long salt water prevention dyke will have affect on its ecosystem. Analyzing fish specimens collected from 2005 to 2007 in Tam Giang - Cau Hai lagoon, we revealed 177 species belonging to 129 genus of 73 families in 18 orders, of those the Perciformes are the most abundant order with 100 species (56.50%); the next is Cypriniformes with 15 species (8.47%), Anguilliformes with 12 species (6.78%), Clupeiformes with 9 species (5.08%); Pleuronectiformes order with 8 species (4.52%); each of Scorpaeniformes and Tetraodontiformes order with 5 species (2.82%); Siluriformes and Beloniformes with 4 species (2.26%); Rajiformes and Synbranchiformes with 3 species (1.69%); each of Elopiformes and Syngnathiformes with 2 species (1.13%); and the others with 1 species (0.56%). Of the total 177 fish species recorded in Tam Giang - Cau Hai lagoon, there are 21 species of the local economic value and 8 species listed in Red Data Book of Vietnam (2007) at different levels (VU - Vulnerable and EN - Endangered).